A New Architecture of Facilities for Low-Income Countries. (Policy Papers; Policy Paper ;, 2009)
This paper proposes a new facilities architecture for Low-Income Countries. It is based on "Option 2" set out in the framework paper discussed by the Executive Board on March 20, 2009. The new architecture provides a unified facilities framework for LICs under a new Poverty Reduction and Growth Trust (PRGT). The facilities are distinguished primarily by the duration of the financing and adjustment needs and the conditionality standard.